2014
DOI: 10.4209/aaqr.2013.05.0157
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Measurement of Carbon Monoxide in Rural Indian Woman Exposed to Different Cooking Fuel Smoke

Abstract: In India more than 70% of the population use biomass fuels for cooking. Women, who traditionally carry out the cooking in this culture, experience the highest lifetime Carbon Monoxide (CO) exposure due to the burning of such fuels in traditional stoves. CO levels were measured in this study in the breathing zone atmosphere of cooks during the cooking cycle, using different fuels such as LPG, wood, crop residues and dung cakes, in a rural area of the National Capital Region (NCR) of India. The exhaled breath CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Of the 10 subjects with abnormal spirometry (Table 2) Similarly, studies from North India reported higher pollution levels in kitchens using SBFs (SBF: LPG-774:25 µg/m 3 of PM 2.5 and 33.5: 0.44 ppm of CO). 4,47,48,69 Statistically, a significant difference was found in FEV 1 , whereas for FVC, the difference was not significant (P = .08). Moreover, the proportion of subjects with obstructive defects was higher among SBF and mix fuel users, as compared with LPG users.…”
Section: Lung Function Assessmentmentioning
confidence: 82%
“…Of the 10 subjects with abnormal spirometry (Table 2) Similarly, studies from North India reported higher pollution levels in kitchens using SBFs (SBF: LPG-774:25 µg/m 3 of PM 2.5 and 33.5: 0.44 ppm of CO). 4,47,48,69 Statistically, a significant difference was found in FEV 1 , whereas for FVC, the difference was not significant (P = .08). Moreover, the proportion of subjects with obstructive defects was higher among SBF and mix fuel users, as compared with LPG users.…”
Section: Lung Function Assessmentmentioning
confidence: 82%
“…There have been numerous studies that have used different approaches to assess indoor and outdoor induced environmental health risks, including domestic firewood induced air pollution, for example Kapwata et al [3], Olave et al [4], Mitchell et al [5], Parajuli et al [6], Jung et al [7] and Joon et al [8], to name a few. It is evident from that these studies inferred on air pollution induced health risk from a one sided and narrow methodological base.…”
Section: Introductionmentioning
confidence: 99%
“…The research methodology received ethical clearance from The University of Queensland's human ethics committee 26 following all the guidelines provided to ensure that research participants are exposed to no harm or embarrassment. To comply with the university's research ethics guidelines, three important stages employed during the fieldwork are discussed below.…”
Section: Ethical Considerationsmentioning
confidence: 99%